Systemic Lupus Erythematosus and Common Variable Immunodeficiency. Issue 1 (January 2022) - Azar, Antoine; Aldaoud, Nawras; Hardenbergh, Dylan; Krimins, Rebecca; Son, James; Shiroky, Jennifer; Timlin, Homa
Abstract : Abstract: Systemic lupus erythematosus (SLE) and common variable immunodeficiency (CVID) are both conditions defined by immune system dysfunction: one hyperactive, the other hypoactive. Although uncommon, these diseases can coexist in the same individual. This review aims to assess the state of the literature on the relationship between SLE and CVID, particularly when workup for CVID should be considered in individuals with SLE and how CVID in individuals with SLE should be treated. Abstract : Supplemental digital content is available in the text.